Drinking water quality in the alpine pastures of the eastern Tibetan plateau - Sillanpää, Mika; Hulkkonen, Riina-Maarit; Manderscheid, Angela (Rangifer, 2004)
The need for water quality research on the Tibetan plateau has arisen after the rangeland was allocated and leased as pasture grounds to individual nomadic families in the 1990s. These policies changed the access to water sources. The imposed fencing of the pasture tenures makes the situation even more delicate. Nomadic families are now obliged to use only water sources existing on their own site. The restrictions have caused the urge to use all available water, which resulted in increasing water quality and quantity problems. In the past, natural water sources were in common use. During the Collective era, machine-dug wells near the collective settlements facilitated the procurement of drinking water. Based on recent investigations in Dzoge county (Sichuan province), the nomadic families of some regions considered the availability of adequate drinking water for humans and animals as their biggest problem. For this study, eight water samples were collected from the Dzoge county area. All samples were from different kinds of sources, but all in continuous use by humans and animals. The samples were analyzed for typical potable water quality factors (hygienic and technique-aesthetic). The results show that the Chinese national guideline values were exceeded for NO4-N and PO4-P in most open sampling locations. Those parameters do not spoil the water by themselves, but together with suspended solids and organic materials produce a great environment for bacteria like E. coli and fecal streptococci to grow. The result analysis and pictures seen from the location reveal that bacterial growth may be the biggest problem in water quality. Even primitive protection around the water source (i.e. concrete rings, wooden barriers around edges, covers) seem to have a great impact on water quality.